Mechanical and thermal properties of nanocarbon-reinforced aluminum matrix composites at elevated temperatures. (1st December 2016) - Shin, S.E.; Ko, Y.J.; Bae, D.H.
Abstract: This study evaluated the mechanical and thermal properties of aluminum alloy 2024 (Al2024) matrix composites reinforced with multi-walled carbon nanotube (MWCNT) or few-layered graphene (FLG) in the temperature range of 250–430 °C. The Al2024/MWCNT and Al2024/FLG composites were fabricated using powder metallurgy, and the associated microstructures were observed. At 350 °C, both composites maintain high yield stress about 110 MPa, since uniform dispersion of the nano-scale reinforcements has a strong interface, hinders the dislocation movement and eutectic phase coarsening and severe softening of the matrix. The composites also show a low thermal expansion coefficient of ∼18×10 −6 / K . The results are respectively over ∼2.5 times higher strength and ∼20% lower CTE than those of commercial Al alloy used as piston material (AlSi12 CuMgNi).